Karakteristrik Enkapsulat Ekstrak Pewarna Fungsional Bunga Rosella (Hibiscus sabdariffa L.) pada Perlakuan Perbandingan Kasein-Maltodekstrin - Ariyanti Lestari, Putu Dwi; Wrasiati, Luh Putu; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
Rosella contains high levels of anthocyanin and can be used as a source of functional dyes. The making of functional dyes is carried out through the process of extraction and encapsulation. The aim s of this study were to determine the effect of casein-maltodextrin encapsulation ratio on the encapsulation characteristics of rosella flower functional dye extract and determine the best encapsulation ratio of casein-maltodextrin in producing rosella functional dye extract encapsulates. Experiments in this study used a single factor randomized block design. These factors are the casein and maltodextrin ratio which consists of (maltodextrin), (1: 0.5), (1: 1), (1: 1.25), (1: 1.5), (1: 1.75), (1: 2.0) , (1: 2.5) and (casein) . The results showed that casein and maltodextrin comparison factors had a significant effect of yield, (P <0.01) on yield, total anthocyanin, surface anthocyanin level, encapsulation efficiency, solubility, brightness (L * ), redness (a*), yellowish level (b*) but did not have a significant effect (P> 0 . 05) on water content. The comparison treatment between casein and maltodextrin 1: 0.5 is a treatment to produce encapsulate products of roselle flower functional dye extract with a yield of 42.86 percent, water content of 5.04 percent, surface anthocyanin total of 9.43 mg/g, surface anthocyanin level 1.66 mg/g, encapsulation efficiency 82.37 percent, solubility 45.84 percent, brightness level (L*) 60.86, redness level (a*) 25.64, yellowish level (b*) 29.61. Keywords: rosella (Hibiscus sabdariffa L.), extraction, casein, maltodextrin, encapsulation.